Epigenomic enhancer annotation reveals a key role for NFIX in neural stem cell quiescence - Martynoga, Ben; Mateo, Juan L.; Wittbrodt, Joachim; Ettwiller, Laurence (Genes & development, 2013)
A biweekly scientific journal publishing high-quality research in molecular biology and genetics, cancer biology, biochemistry, and related fields